Peran Servicescape dalam Meningkatkan Kualitas Pelayanan Hotel Mewah: Studi Kasus di Four Seasons Resort Bali - Ni Komang Tia Anggreni; Irene Hanna H. Sihombing; Ni Made Suastini (Bogor Hospitality Journal, 2025)
This study examines the impact of servicescape on service quality at Four Seasons Resort Bali at Jimbaran Bay. A quantitative approach was employed, utilizing primary data collected from 100 guests who completed questionnaires. The analysis was conducted using simple linear regression with SPSS version 23. The results reveal a significant positive influence of servicescape on service quality, with a significance value of 0.000 (<0.05) and a coefficient of determination (R²) of 0.458, indicating that 45.8% of the variation in service quality is explained by servicescape. Elements such as lighting, scent, and temperature were rated highest for atmospheric comfort, while physical facilities such as room condition and completeness received the lowest scores. The study concludes that servicescape significantly influences service quality and provides recommendations for management to enhance the physical environment to better meet guest expectations.